2022
DOI: 10.1007/s11104-022-05758-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variation of surface soil hydraulic properties under different tillage and maize-based crop sequences in a Mediterranean area

Abstract: Aims The surface crust formed by the drop impact of rainfall and/or irrigation is a prevalent characteristic in many Mediterranean soils. However, the temporal variation of soil hydraulic properties induced by surface crust during the high-frequency irrigation has rarely been investigated. Methods Beerkan infiltration tests in conjunction with the BEST method were used to investigate the effects of surface crusting on the spatio-temporal variation of satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Soil characteristics such as silt and clay content increase crusting, while factors like aggregate stability and organic matter content mitigate it, highlighting the complex interplay of soil properties in crusting susceptibility (Chen et al 2013). In this issue, Talukder et al (2022) investigated the temporal variation of soil hydraulic properties induced by surface crust in Mediterranean soils in NE Spain during high-frequency irrigation. Using Beerkan infiltration tests and the BEST method, this study revealed that intensive tillage initially elevated both saturated soil hydraulic conductivity and sorptivity compared to autumn tillage, but these values declined after a 60-day period.…”
Section: Impacts On Soil Hydraulic Propertiesmentioning
confidence: 99%
“…Soil characteristics such as silt and clay content increase crusting, while factors like aggregate stability and organic matter content mitigate it, highlighting the complex interplay of soil properties in crusting susceptibility (Chen et al 2013). In this issue, Talukder et al (2022) investigated the temporal variation of soil hydraulic properties induced by surface crust in Mediterranean soils in NE Spain during high-frequency irrigation. Using Beerkan infiltration tests and the BEST method, this study revealed that intensive tillage initially elevated both saturated soil hydraulic conductivity and sorptivity compared to autumn tillage, but these values declined after a 60-day period.…”
Section: Impacts On Soil Hydraulic Propertiesmentioning
confidence: 99%
“…3c). Spatial variations of K(Ψ) might be due to presence of plant roots and its growth and development W-row that creates preferential flow channels (Talukder et al, 2022a). Therefore, soil water flow is significantly greater along the root-soil interface (W-row) than distant from the plants (B-row) (Zhang et al, 2017).…”
Section: Position Effectsmentioning
confidence: 99%
“…On the other hand, differences in hydraulic properties tend to become insignificant a few months after the last tillage, even when comparing treatments such as conventional and untilled [6,9]. However, soils treated with minimum tillage or untilled are less prone than those treated with conventional tillage to surface crust formation [10] and can lead to progressive increases in SOC [11].…”
Section: Introductionmentioning
confidence: 99%